FRI0419 Association between Objectively Assessed Physical Activity and Disease Progression in A Population Based Sample of Ankylosing Spondylitis Patients. (15th July 2016) - Khan, H.I.; Aitken, D.; Lewis, P.; Zochling, J.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic, systemic disease that is characterized by inflammation, especially at the spinal column. Chronic inflammation of the spinal and extraspinal joints and enthesis frequently lead to limitation of spinal and joint mobility. Although AS results in decreased physical and functional capacity, recent studies have suggested that physical activity (PA)/exercise is as crucial as drug treatment in the management of AS [1, 2]. However the relationship between PA and AS disease activity remain s uncertain as the studies conducted thus far have used non-objective measures to assess PA. Objectives: The aim of this study was to examine the association between PA at baseline and AS disease progression over 2 years especially in male participants. Methods: 113 participants, initially recruited if they had inflammatory back pain or extra-articular features of AS for 10 years or less, were studied at baseline and 2 years. PA was assessed at the baseline visit only using a pedometer (steps/day) over 10 days. MRI scans of the spine were performed to assess inflammation at baseline and 2 years. Images were scored, using the Spondyloarthritis Research Consortium of Canada method. Disease activity, functional limitations and mobility were assessed at both time points using the Bath AS Disease Activity Index (BASDAI), Bath AS Functional Index (BASFI) and Bath AS Metrology Index (BASMI) respectively. Results: 113 participants [mean-age (years) 41 (range 17–72); 64% male, BMI 27 (18–54)] were studied at baseline and two years. 62% of the participants had radiographic evidence of AS according to the modified New York criteria. 100 participants showed some evidence of spinal inflammation (mean 9.86 (0–60)). Mean steps/day were 4665 (1666–9711). Higher number of steps/day at the baseline visit showed an independent negative association with change in spinal MRI inflammation (β (per 1000 steps) = -0.49 (-0.91, -0.07) over 2 years. Further analysis (figure-1 ) showed a dose response relation between PA and change in spinal inflammation. Participants who had an increase in severity of inflammation had on average least number of steps/day, whereas participants who had a decrease in severity of inflammation had the highest number of steps/day at the baseline visit. Higher number of steps/day at the baseline visit were negatively associated with change in BASDAI (β (per 1000 steps) = -0.33 (-0.66, -0.04) score over 2 years. However we did not see any significant associations between PA and changes in BASFI and BASMI scores. We further explored sex interactions for the associations between PA and changes in spinal inflammation and BASDAI scores, and found that higher number of steps/day resulted in a significantly higher decrease in the severity of MRI inflammation and BASDAI scores (p<0.05) in the male participants. Conclusions: Higher PA was associated with a decrease in disease activity both clinically and on imaging. References: Heikkila S, Viitanen JV, Kautiainen H, Kauppi M. Sensitivity to change of mobility tests; effect of short term intensive physiotherapy and exercise on spinal, hip, and shoulder measurements in spondyloarthropathy. J Rheumatol. 2000; 27:1251–6. Ince G, Sarpel T, Durgun B, Erdogan S. Effects of a multimodal exercise program for people with ankylosing spondylitis. Phys Ther. 2006; 86:924–35. Disclosure of Interest: None declared